The Church and Northern English Society in the Fourteenth Century : The Archbishops of York and Their Records. - Dryburgh, Paul.; Rees Jones, Sarah; Harvey, Katherine; Hayes, Rosemary C. E.; Jenkins, John.; Lee, John S.; Mackman, Jonathan; Perring, Stefania Merlo; McHugh, Jenny M.; Sneddon, Shelagh (Woodbridge : York Medieval Press, 2024)
Insights into ecclesiastical, political, cultural and social history of the north of England through an exploration of the administrative archives of fourteenth century archbishops.
Frontmatter -- Contents -- List of Illustrations -- List of Contributors -- Acknowledgements -- List of Abbreviations -- Map: The Ecclesiastical Province of York, c. 1304-1405 -- Introduction -- 1 The Administrative Records of the Archbishops of York, 1304-1405 -- 2 The Archbishops of York and the Government of Fourteenth-Century England -- 3 Support or Scourge? Archbishop William Melton and the Tradition of Loyal Opposition to the English Crown, 1317-1340 -- 4 Beyond the Border: The Influence of York Clerks in the Two Edwards' Scottish Administrations, 1332-1357 -- 5 Responding to Royal Requirements: Clerical Taxation in the Province of York, 1304-1405 -- 6 Ad insolenciam ipsius rebellis salubrius reprimendam: William Thorntoft, the Abbey of Rufford and Significations of Excommunication in the Northern Province -- 7 Blood, Sex and Holy Water: Reconciling Churches and Churchyards in the Medieval Diocese of York -- 8 Structuring Episcopal Authority: Palaces and Residences of the Archbishop of York -- 9 Medieval Parks of the Archbishops of York -- 10 Northern Ways? Pilgrimage, Politics and Piety in the Fourteenth-Century Administrative Records of the Archdiocese of York -- 11 Underexplored Sources for Gender History: New Approaches to the Fourteenth-Century York Archbishops' Registers -- 12 Joan of Leeds and other Apostate Nuns in the Province of York, 1300-1350 -- Bibliography of Records of the Archbishops of York, 1304-1405 -- Index
Description based on publisher supplied metadata and other sources.
Includes bibliographical references and index.
JSTOR
Keywords: Catholic Church. -- Province of York (England) -- History -- 14th century; Christianity and culture -- History -- Middle Ages, 600-1500.; Christianity and culture -- England -- History; York (England) -- Church history -- 14th century; Great Britain -- History -- 14th century; Grande-Bretagne -- Histoire -- 14e siècle.; Christianisme et civilisation -- Angleterre -- Histoire; HISTORY / Europe / Great Britain / Norman Conquest to Late Medieval (1066-1485).; Alexander Neville; Apostasy; Archbishop Richard Scrope; Archbishop William Greenfield; Archbishop William Melton; Carlisle; Clerical Taxation; Durham; Edward II; Edward III; Excommunication; Henry IV; John Thoresby; Pilgrimage; Robert Waldby; Thomas Arundel; Thomas, earl of Lancaster; William Zouche